2.45 GHz microwave radiation impairs learning and spatial memory via oxidative/nitrosative stress induced p53-dependent/independent hippocampal apoptosis: Molecular basis and underlying mechanism - Shahin S.; Banerjee S.; Singh S.P.; Chaturvedi C.M. (My University, 2025)
A close association between microwave (MW) radiation exposure and neurobehavioral disorders has been postulated but the direct effects of MW radiation on central nervous system still remains contradictory. This study was performed to understand the effect of short (15 days) and long-term (30 and 60 days) low-level MW radiation exposure on hippocampus with special reference to spatial learning and memory and its underlying mechanism in Swiss strain male mice, Mus musculus. Twelve-weeks old mice were exposed to 2.45 GHz MW radiation (continuous-wave [CW] with overall average power density of 0.0248 mW/cm2 and overall average whole body specific absorption rate value of 0.0146 W/Kg) for 2 h/day over a period of 15, 30, and 60 days). Spatial learning and memory was monitored by Morris Water Maze. We have checked the alterations in hippocampal oxidative/nitrosative stress, neuronal morphology, and expression of pro-apoptotic proteins (p53 and Bax), inactive executioner Caspase- (pro-Caspase-3), and uncleaved Poly (ADP-ribose) polymerase-1 in the hippocampal subfield neuronal and nonneuronal cells (DG, CA1, CA2, and CA3). We observed that, short-term as well as long-term 2.45 GHz MW radiation exposure increases the oxidative/nitrosative stress leading to enhanced apoptosis in hippocampal subfield neuronal and nonneuronal cells. Present findings also suggest that learning and spatial memory deficit which increases with the increased duration of MW exposure (15 < 30 < 60 days) is correlated with a decrease in hippocampal subfield neuronal arborization and dendritic spines. These findings led us to conclude that exposure to CW MW radiation leads to oxidative/nitrosative stress induced p53-dependent/independent activation of hippocampal neuronal and nonneuronal apoptosis associated with spatial memory loss. © The Author 2015. Published by Oxford University Press on behalf of the Society of Toxicology. All rights reserved..